FARMERS' BEHAVIOR IN DEVELOPING LOCAL DUCK FARMING ON THE COAST OF LAKE TONDANO - Elly, Femi (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2024)
Duck farming produces technological products such as DOD, ducks and eggs which were related to food availability based on food security and independence, as well as improving food quality and safety. The local duck business on the coast of Lake Tondano, Minahasa Regency was an activity that has long been carried out to support the family economy. The problem was how far the farmer's behavior was in developing local ducks. The aim of this research was to examine the behavior of duck farmers in an effort to develop local duck. The research method used was a survey method located on the coast of Lake Tondano. The number of respondents was 30 farmers who breed local ducks in rice fields. The data analysis used was descriptive analysis. The research results show that 100% of farmers on the coast of Lake Tondano develop local duck businesses in a traditional and unsustainable manner. Ducks were grazed in rice fields after the rice harvest. The food consumed was small animals including pests and rice plant residues that fall after harvest, plus snails (in the research area called